Step
*
2
of Lemma
m-sup-property
1. [X] : Type
2. d : metric(X)
3. mtb : m-TB(X;d)
4. f : X ⟶ ℝ
5. mc : UC(f:X ⟶ ℝ)
6. ∀x:ℝ. ((∃x@0:X. (x = (f x@0))) 
⇒ (x ≤ m-sup{i:l}(d;mtb;f;mc)))
7. ∀e:ℝ. ((r0 < e) 
⇒ (∃x:ℝ. ((∃x@0:X. (x = (f x@0))) ∧ ((m-sup{i:l}(d;mtb;f;mc) - e) < x))))
8. e : ℝ
9. r0 < e
10. ∃x:ℝ. ((∃x@0:X. (x = (f x@0))) ∧ ((m-sup{i:l}(d;mtb;f;mc) - e) < x))
⊢ ∃x:X. ((m-sup{i:l}(d;mtb;f;mc) - e) < (f x))
BY
{ (ExRepD THEN RenameVar `z' (-3) THEN D 0 With ⌜z⌝  THEN Auto) }
Latex:
Latex:
1.  [X]  :  Type
2.  d  :  metric(X)
3.  mtb  :  m-TB(X;d)
4.  f  :  X  {}\mrightarrow{}  \mBbbR{}
5.  mc  :  UC(f:X  {}\mrightarrow{}  \mBbbR{})
6.  \mforall{}x:\mBbbR{}.  ((\mexists{}x@0:X.  (x  =  (f  x@0)))  {}\mRightarrow{}  (x  \mleq{}  m-sup\{i:l\}(d;mtb;f;mc)))
7.  \mforall{}e:\mBbbR{}.  ((r0  <  e)  {}\mRightarrow{}  (\mexists{}x:\mBbbR{}.  ((\mexists{}x@0:X.  (x  =  (f  x@0)))  \mwedge{}  ((m-sup\{i:l\}(d;mtb;f;mc)  -  e)  <  x))))
8.  e  :  \mBbbR{}
9.  r0  <  e
10.  \mexists{}x:\mBbbR{}.  ((\mexists{}x@0:X.  (x  =  (f  x@0)))  \mwedge{}  ((m-sup\{i:l\}(d;mtb;f;mc)  -  e)  <  x))
\mvdash{}  \mexists{}x:X.  ((m-sup\{i:l\}(d;mtb;f;mc)  -  e)  <  (f  x))
By
Latex:
(ExRepD  THEN  RenameVar  `z'  (-3)  THEN  D  0  With  \mkleeneopen{}z\mkleeneclose{}    THEN  Auto)
Home
Index